2008
DOI: 10.1103/physrevb.78.064519
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the pressure dependences ofTcin the trivalentd-electron superconductors Sc, Y, La, and Lu up to megabar pressures

Abstract: Whereas dhcp La superconducts at ambient pressure with T c ≃ 5 K, the other trivalent d-electron metals Sc, Y, and Lu only superconduct if high pressures are applied. Earlier measurements of the pressure dependence of T c for Sc and Lu metal are here extended to much higher pressures. Whereas T c for Lu increases monotonically with pressure to 12.4 K at 174 GPa (1.74 Mbar). T c for Sc reaches 19.6 K at 107 GPa, the 2nd highest value observed for any elemental superconductor. At higher pressures a phase transit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 49 publications
3
48
1
Order By: Relevance
“…Binary compounds were reported to superconduct at surprisingly high critical temperatures (T c 's) reaching 40 K for MgB 2 [1], as well as the highest ever obtained T c of ∼200 K in SH 3 at an (extreme) pressure of p 200 GPa [2]. The basic elements with high T c 's include Li (T c ≈ 15-20 K at 30 GPa) [3][4][5], Ca (T c ≈ 21-29 K at 220 GPa) [6], Sc and Y (T c ≈ 20 K near 100 GPa) [7,8], V (T c ≈ 17 K at 120 GPa) [9,10], and S (T c ≈ 17 K at 220 GPa) [11]. Such high transition temperatures of basic elements indicate the importance of pressure as a tuning parameter of superconducting properties and its role in unraveling the intrinsic properties of the electronic system.…”
mentioning
confidence: 82%
“…Binary compounds were reported to superconduct at surprisingly high critical temperatures (T c 's) reaching 40 K for MgB 2 [1], as well as the highest ever obtained T c of ∼200 K in SH 3 at an (extreme) pressure of p 200 GPa [2]. The basic elements with high T c 's include Li (T c ≈ 15-20 K at 30 GPa) [3][4][5], Ca (T c ≈ 21-29 K at 220 GPa) [6], Sc and Y (T c ≈ 20 K near 100 GPa) [7,8], V (T c ≈ 17 K at 120 GPa) [9,10], and S (T c ≈ 17 K at 220 GPa) [11]. Such high transition temperatures of basic elements indicate the importance of pressure as a tuning parameter of superconducting properties and its role in unraveling the intrinsic properties of the electronic system.…”
mentioning
confidence: 82%
“…, ScBX(10), ScGeX(9), ScFeX(7) and ScCX(6) systems. Simultaneously the number of synthesized ternary compounds has doubled, reaching over a thousand.Kotur pointed out the regularity of the occurrence of a large number of compounds on some characteristic cross section of phase diagrams.…”
mentioning
confidence: 99%
“…All of three are considered to belong to a group that exhibits the increase in T c under the HP circumstances. 22) Indeed, smooth linear-increase in T c is observed only in V. All previous studies for V have reported the positive dT c /dP coefficient. 3,2327) According to the study of Struzhkin et al, nonstrained Nb shows the increase in T c after its slight decrease, Fig.…”
Section: Introductionmentioning
confidence: 85%
“…In the periodic table containing 118 elements, there are 29 superconductors at ambient pressure, and 11 elements of them exhibit the increase in T c under hydrostatic pressure (HP). 21,22) Three fifth-element superconductors such as V, Nb, and Ta has nominal T c of 5.3 K, 9.2 K, and 4.5 K, respectively. Previous studies of HP compression for V, Nb, and Ta are summarized in Tables 1, 2, and 3, respectively.…”
Section: Introductionmentioning
confidence: 99%